2014
DOI: 10.1158/1078-0432.ccr-14-1134
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of NANOG/NANOGP8 Downregulates MCL-1 in Colorectal Cancer Cells and Enhances the Therapeutic Efficacy of BH3 Mimetics

Abstract: Purpose High levels of BCL-2 family members in colorectal carcinoma cause resistance to treatment. Inhibition of NANOG or its paralog NANOGP8 reduces the proliferation, stemness, and tumorigenicity of colorectal carcinoma cells. Our hypothesis was that inhibition of NANOG/NANOGP8 enhances the cytotoxic effect of BH3 mimetics targeting BCL-2 family members in colorectal carcinoma cells through reducing expression of MCL-1, a prosurvival BCL-2 protein. Experimental Design Lentiviral vector (LV) shRNA to NANOG … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 39 publications
(53 reference statements)
3
26
0
Order By: Relevance
“…Inhibition of MCL-1 sensitizes cancer cells to chemotherapeutic drugs and IR (12,(14)(15)(16). Consistent with the current literature, we found that MCL-1 depletion ( Fig.…”
Section: Resultssupporting
confidence: 92%
“…Inhibition of MCL-1 sensitizes cancer cells to chemotherapeutic drugs and IR (12,(14)(15)(16). Consistent with the current literature, we found that MCL-1 depletion ( Fig.…”
Section: Resultssupporting
confidence: 92%
“…High level of c-FLIP may protect cancer cells from the apoptotic signaling exists in circumstance. Therefore, reducing the expression of c-FLIP in tumor cells is able to improve the sensitivity of them to drugs [29,30]. In this study, we demonstrated that overexpression of c-FLIP in HCC can be abolished by miR-382 introduction.…”
Section: Mir-382-overexpressed Hcc Model Is Sensitive To γδ T Cells Tmentioning
confidence: 57%
“…Interestingly, although Mcl-1 had previously been shown to confer resistance to ABT-737 and ABT-199 in other hematological malignancies and solid tumors, 10,[18][19][20]43,44 its role in mediating resistance in CLL had remained somewhat controversial. For example, in the study of Vogler et al, 15 induction of Mcl-1 expression by stimulation with interleukin-4 or interferon-g was associated with only marginal protection, prompting the authors to conclude that resistance to ABT-737 in CLL is largely Mcl-1 independent.…”
Section: Discussionmentioning
confidence: 99%
“…17 Previous studies by our group have shown that sustained engagement of the BCR induces Mcl-1, 6 and high levels of Mcl-1 were shown to inversely correlate with treatment response in the phase 1 study of ABT-263 in CLL. 12 In addition, high levels of Mcl-1 have been shown to protect other hematological malignancies and certain solid tumors from ABT-199, [18][19][20] suggesting that Mcl-1 could also confer ABT-199 resistance to CLL cells. To further explore this possibility, we evaluated whether BCR-induced Mcl-1 overexpression can protect CLL cells from ABT-199 and whether this protection can be overcome by available BCR signaling inhibitors.…”
mentioning
confidence: 99%